Internalization Of Moral Feelings As The Basis For Character Building And Accountability Of Islamic Boarding School Students - Mubarok, Husni; Baihaqi, Jadzil; Anggraini, Dian Mustika (Jurnal Penelitian, 2025)
This study explores the internalization of moral feeling as the basis for shaping the accountability character of students at Pesantren Darur Ridwan Al-Fadholi, Pati. Using a qualitative descriptive approach, data were collected through interviews, observations, and documentation with the pesantren leaders, teachers, and students. The findings reveal four interrelated dimensions of accountability: institutional, individual, spiritual, and social. Institutional accountability is reflected in financial transparency and reporting practices, while individual accountability is fostered through students’ direct involvement in managing pesantren business units that require honesty and responsibility. Spiritual accountability is manifested in the habituation of religious practices, such as congregational prayers, Qur’an recitation, and tahfidz programs, which cultivate the awareness of accountability before Allah. Social accountability emerges through students’ participation in community activities, shaping their sense of responsibility beyond the pesantren environment. The study concludes that accountability in pesantren cannot be built solely on formal systems, but must be reinforced through the deep internalization of moral feelings. This research contributes theoretically by integrating moral psychology and Islamic accountability, and practically by offering insights for pesantren to strengthen both affective character formation and institutional systems of transparency.